Habitat‐dependent interactive effects of a heatwave and experimental fertilization on the vegetation of an alpine mire. (17th May 2013) - Brancaleoni, Lisa; Gerdol, Renato; Halvorsen, Rune
Abstract Aims Our objective was to investigate how the after‐effects of a heatwave interacted with nutrient addition in affecting the vegetation of an alpine mire. We also aimed to assess if the responses of vegetation to the environmental changes differed between mire habitats. Location A mire in the Dolomites (southeastern Alps, Italy, 1800 m a.s.l.). Methods We carried out an 8‐yr (2002–2009) experiment of nutrient addition in an alpine mire that experienced, in summer 2003, an unprecedented heatwave. The cover of vascular plants and mosses was assessed non‐destructively and the presence of all vascular plant and moss species was recorded in 60 plots. Results Interacting effects of the heatwave and experimental fertilization brought about profound changes in the vegetation of the mire. Patterns of change varied considerably between two habitats (hummocks and lawns). In the short term (2003–2005), the 2003 heatwave triggered a change in vegetation structure and PFT cover, with vascular plants expanding at the expense of mosses in both habitats. In the mid‐term (2005–2009), moss cover increased in hummocks because Sphagnum mosses recovered and non‐Sphagnum mosses expanded, especially under N addition. Conversely, in lawns vascular plants expanded while mosses did not recover. These trends were strengthened when N was added with no concomitant P addition. A decline in species richness was observed in lawns, most likely due to stronger interactions among species. Conclusions Hummocks have a greater ability than lawns to recover from extreme climatic events under higher levels of N influx. Conversely, a persistent increase in vascular plant cover at the expense of moss cover in lawns may jeopardize the carbon sink function of lawn habitats.